Comparative Effects of Nitrogen Fertigation and Granular Fertilizer Application on Pepper Yield and Soil GHGs Emissions - Antonio Manco; Matteo Giaccone; Luca Vitale; Giuseppe Maglione; Maria Riccardi; Bruno Di Matteo; Andrea Esposito; Vincenzo Magliulo; Anna Tedeschi (Horticulturae, 2025)
Quantitative greenhouse gas (GHG) budgets for Mediterranean pepper cultivation are still missing, limiting evidence-based nitrogen management. Furthermore, mitigation value of fertigation respect to granular fertilization in vegetable systems remains uncertain. This study therefore compared the GHG footprint and productivity of ‘papaccella’ pepper under two nitrogen fertilization methods: granular fertilization versus low-frequency fertigation with urea, each supplying about 63 kg N ha−1. Eight automated static chambers coupled to a cavity ring-down spectrometer monitored soil CO2 and N2O fluxes throughout the season. Cumulative emissions did not differ between treatments (CO2: 811 ± 6 g m−2 vs. 881 ± 4 g m−2; N2O: 0.038 ± 0.008 g m−2 vs. 0.041 ± 0.015 g m−2, fertigation vs. granular), and marketable yield remained at ~11 t ha−1, leaving product-scaled global warming potential (GWP) unchanged. Although representing less than 2% of measured fluxes, “hot moments,” burst emissions exceeding four standard deviations (SD) from the mean, accounted for up to 4% of seasonal CO2 and 19% of N2O. Fertigation doubled the frequency of these events but reduced their peak magnitude, whereas granular application produced fewer but more extreme bursts (>11 SD). Results showed that fertigation did not mitigate GHGs emission nor improve productivity for Mediterranean pepper, mainly due to the low application frequency and the use of a urea fertilizer. Moreover, we can highlight that in horticultural systems, omitting ‘hot moments’ leads to systematic underestimation of emissions.